Association of leptin, resistin, and high-molecular-weight adiponectin levels with psoriasis area and severity index scores, obesity, and insulin resistance in psoriasis patients - Emine Müge Acar; Nilsel İlter; Şehri Elbeg (Wolters Kluwer Medknow Publications, 2019)
Background: Psoriasis is frequently associated with obesity and cardiovascular diseases. Adipocytokines have been implicated in the pathogenesis of psoriasis and its cardiometabolic comorbidities. Objectives: The aim of this study was to assess the roles of leptin, resistin, and high-molecular-weight (HMW) adiponectin in psoriasis as well as their relationship with Psoriasis Area and Severity Index (PASI), obesity, and insulin resistance. Materials and Methods: Forty-six psoriasis patients and equivalent age-, sex-, and body mass index (BMI)-matched controls were recruited in this study. PASI, waist and hip circumferences, and waist/hip ratio (WHR) were recorded, and total body fat mass (TBFM) values were measured using a bioimpedance body composition analyzer. Fasting serum leptin, resistin, and HMW adiponectin levels were measured, and homeostasis model assessment values for insulin resistance (HOMA-IR) were calculated. Results: After the adjustment for anthropometric variables, leptin levels did not differ significantly between the groups (P = 0.736). The patient group showed significantly elevated resistin and lower HMW adiponectin levels (P = 0.007, P= 0.010, respectively). The correlation of serum leptin, resistin, and HMW adiponectin with PASI was not significant (r = −0.100, P= 0.506; r = −0.053, P= 0.726; r = −0.103, P= 0.494, respectively). HOMA-IR positively correlated with leptin and negatively correlated with HMW adiponectin (r = 0.426, P < 0.001; r = −0.393, P < 0.001, respectively). The correlation of leptin and resistin with BMI was direct while that of HMW adiponectin with BMI was inverse (r = 0.532, P < 0.001; r = 0.240, P= 0.021; r = −0.408, P < 0.001, respectively). No significant differences were detected regarding TBFM, and waist and hip circumferences (P = 0.187, P = 0.090, P= 0.543, respectively). However, WHR was significantly higher in the patient group (P = 0.015). Conclusion: Altered adipocytokine levels in psoriasis patients suggest a possible role of adipocytokines in the relationship between psoriasis and its metabolic comorbidities. Fat distribution is also different from the healthy population with similar TBFM values, and abdominal obesity, which is an independent cardiovascular risk factor, is more prevalent in psoriasis patients.